Status and causes of rice loss in Vietnamese rice processors : a case study on Vietnamese rice processor in Mekong Delta, Vietnam : a thesis presented in partial fulfillment of the requirements of the degree of Master of Food Technology at Massey University, Manawatu, New Zealand - Ngo, Vy Thi Thuy (Massey University, 2025)
Background and Objective: The loss of rice during processing is an important issue for Vietnam's agricultural economy, especially in the Mekong Delta region, which contributes significantly to national rice production. This study aims to analyze the situation and the primary sources of rice processing loss in Vietnam's rice processors through a comprehensive case study of CDo Company, a medium-sized rice processing facility located in the Mekong Delta with an annual processing capacity of 45,000 tons. Methods: The evaluation of rice loss for this study began at the reception of raw paddy rice and ended at the final packaging of rice using direct measurement techniques. Processing data for 36 batches of the Dai Thom 8 variety, each 30,044 kg and constituting about 40% of the facility's production, were analyzed. The study involved monitoring moisture content, calculating yields, assessing quality, and evaluating economic loss. Also, a comparative analysis was carried out using the national standards of Vietnam (TCVN) and other countries (Codex, EU, and Philippines). Results: The investigation uncovered total processing inefficiencies of 21.8% over industry norms. Drying processes incurred a loss of 6.0% on a dry matter basis. In milling processes, 12.7% loss was incurred. The facility's Head Rice Yield (HRY) was 46.0% and the Milled Rice Yield (MRY) was 57.3%. Regarding quality-related losses, 3,869 kg of rice was rejected on account of contamination issues, residue of pesticides, heavy metals, and mycotoxins (Aflatoxin B1, Ochratoxin A). The broken rice ratio to total milled rice reached 19.7%, indicating that the rice was subjected to severe processing damage. Key Findings: The most prominent loss drivers attributed to the poor yield and quality were identified as uncontrolled moisture content, aged drying and milling equipment, contamination of raw materials, as well as poor storage environments. The longer the equipment operates without upgrades and maintenance, the more configuration errors occur, causing greater losses. The economic analysis uncovered processing losses of USD 1,165,631.53 per year for just Dai Thom 8. Recommendations: The research proposes a comprehensive IoT-based action plan to improve processing efficiency and reduce costs through three phases that have taken place in 6-36 months.
Keywords: Vietnam; rice processing; post-harvest losses; Mekong Delta; food security; agricultural technology; processing efficiency; quality control; 300408 Crop and pasture post harvest technologies (incl. transportation and storage); 300207 Agricultural systems analysis and modelling